Implementasi Aplikasi Android dalam Sistem Restock UMKM Maju Jaya Accessories - Zaki, Nurrohmi; Sejati, RR. Hajar Puji (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This research aims to improve the efficiency and effectiveness of the restocking process at UMKM Maju Jaya Accessories through the development of an Android-based application. Previously, the UMKM used a manual restocking method, which often caused delays, stock management errors, and inefficient communication. The designed application allows stores to independently submit restock requests, which can then be monitored in real-time by the business owner. The research methodology uses the Software Development Life Cycle (SDLC) Waterfall model. The results show a significant improvement in stock management timeliness, restocking process efficiency, and a reduction in operational costs that were previously high due to frequent manual errors, such as timing mistakes for stores that were not ready to restock. The application is designed with a simple and user-friendly interface, making it accessible to users from various backgrounds. However, the application is still limited to business owners and partners only and cannot be used publicly. In conclusion, the implementation of this application improves operational effectiveness and provides added value for business owners and partner stores through more efficient and structured stock management.